Effective Use of Lesson Plan to Trigger Students Autonomy - Siti Aimah; Muhimatul Ifadah; Dwi Anggani Linggar Bharati (Universitas Muhammadiyah Semarang, 2016)
Abstract. This study was intended to trigger students autonomy in joining Genre-based Writing class of State Universityof Semarang. Further, it was conducted to know how the students demonstrate their ability in using a set of tactics for taking control of their own learning. For this purpose, 30 students were randomly chosen and two observers involved in lesson study consisted of plan, do, and see. The result showed one of the indicators of succesful teaching and learning in the classroom was not only determined by interaction between the lecturer and the students in the classroom but also the use of lesson plan designed. In triggering the students autonomy in learning, the lecturer established a variety of instructional strategies focusing on academic expectations through the lesson plan. The lecture was designed to engage the students activeness and autonomy so that the goal of learning could be achieved well.